Daily stress appraisals and C-reactive protein in a sample of Black and White women. (September 2021) - Guan, J.Y.; Hamlat, E.; Mujahid, M.; Price, C.; Tomiyama, A.J.; Laraia, B.A.; Epel, E.S.; Mayer, S.E.
Abstract : Introduction: Affective responses to daily stressors have been linked to C-reactive protein (CRP), but associations with cognitive appraisals are rarely examined. This study investigated linkages in a sample of Black and White participants. Methods: Women (159 Black; 163 White; Mage=39) completed daily evening diaries for 3 days assessing perceived stressor demands and coping (control, resources, effectiveness). Participants also provided a fasting blood draw to assess high-sensitivity C-reactive protein (hs-CRP). Multiple linear regression models examined the impact of daily stress appraisals, race, and their interaction with hs-CRP, controlling for education, income, and body mass index. Results: Perceived demands of daily stressors was not significantly related to hs-CRP (p=.450), nor interacted with race (p=.574). Greater perceived coping with daily stressors was associated with lower hs-CRP (p=.038), and this effect was moderated by race (p=.026). Follow-up simple effects analyses showed that this relationship was only significant in White women. Conclusion: For White women, daily positive stress appraisals may buffer stress related inflammation. There may be other determinants in Black women that warrant future research.